Longitudinal data in peripheral blood confirms PM20D1 is a quantitative trait locus (QTL) for Alzheimer's disease and implicates its dynamic role in disease progression: Genetics/genetic factors of Alzheimer's disease. (7th December 2020) - Wang, Qi; Chen, Yinghua; Readhead, Benjamin; Chen, Kewei; Su, Yi; Reiman, Eric M.; Dudley, Joel
Abstract: Background: Genome wide genetic/epigenetic studies are revealing more risk loci associated with the Alzheimer's disease (AD). One recent analysis of human epigenome‐wide association studies (EWAS) reports an association between variations in the gene PM20D1 and AD, showing hypermethylation in the brain tissues in patients with advanced‐stage AD. Methods: We used whole genome DNA methylation data collected from peripheral blood mononuclear cells (PBMCs) in a cohort (n = 649) from the Alzheimer's Disease Neuroimaging Initiative (ADNI) and compared the DNA methylation level at baseline among different diagnosis groups. We also leveraged the longitudinal data up to 4 years, sampled at approximately 1 year intervals to model the alterations in the methylation levels detected at the differentially methylated regions (DMRs) to delineate the methylation change course over aging and disease progression. The dynamic pattern of DNA methylation level with disease progression at the PM20D1 locus in brain tissues were also modeled from the data in The Religious Orders Study and Memory and Aging Project (ROSMAP) Study cohort (n = 740). Results: When compared with controls, patients with mild cognitive impairment (MCI) consistently displayed promoter hypomethylation at reported methylation QTL gene locus PM20D1. This promoter hypomethylation was even more prominent in patients with mild to moderate AD. This is in stark contrast with previously reported hypermethylation in brain tissues in patients with advanced‐stage AD. By leveraging longitudinal DNA methylation data, linear mixed‐effects (LME) modeling for the unchanged diagnosis groups and U‐shape testing for those with changed diagnosis (converters) indicate that, we observe initial promoter hypomethylation of PM20D1 during MCI and early stage AD, which reverses to eventual promoter hypermethylation in the transition to late stage AD. We also confirm this observation in ROSMAP cohort as neuropathology deteriorates. Correlation of DNA methylation between blood and brain tissues at PM20D1 promoter region also demonstrates the pattern is consistent across tissues. Conclusions: Our results confirm that PM20D1 is an mQTL for AD and demonstrate that it plays a dynamic role at different stages of the disease. Further in‐depth study is thus warranted to fully decipher its role in the evolution of AD, and potentially explore its utility as a blood‐based biomarker for AD.